Administración sistémica adjunta de moxifloxacina versus Ciprofloxacina más metronidazol en el tratamiento de periodontitis crónica con presencia de bacilos entéricos gram negativos: I. Efectos clínicos y microbiológicos (2011)
ABSTRACT: Preliminary clinical findings indicate that periodontal lesions associated with Gram-negative enteric rods do not respond to conventional treatment modalities. The aim of the present study was to evaluate and compare the clinical and microbiological effects of scaling and root planing (SRP) combined with systemic administration of moxifloxacin (MOX) or ciprofloxacin plus metronidazole (CIPRO + MET) in the treatment of chronic periodontitis. Methods: seventy-six patients participated in this randomized clinical trial, and they were divided into two groups. Subjects were treated with SRP plus adjunctive MOX (MOX group; n = 38) or SRP plus adjunctive CIPRO + MET (CIPRO + MET GROUP; n = 38). Clinical and microbiological data were recorded at baseline and at 3 and 6 months after treatment. The significant changes in clinical and microbiological parameters between and within the groups were measured using the Mann-Whitney test and Wilcoxon’s rank test respectively. Results: after six months, both treatment groups showed a significant reduction in probing depth and bleeding on probing (P < 0.05) and better clinical attachment. A statistically significant reduction of the proportion of sites > 6 mm was also observed. Gram-negative enteric rods and Aggregatibacter actinomycetemcomitans were not identified in either group six months after baseline. Conclusions: this study provides evidence of the benefit of using MOX or CIPRO+MET as adjunct to SRP in patients with chronic periodontitis harboring Gram-negative enteric rods. However, MOX may be the antibiotic of choice in view of its few adverse effects and single dose treatment per day.